KRITIK TERHADAP PENYEDIAAN RUANG BAGI WANITA DALAM PERUMAHAN REAL-ESTATE - Bharoto Bharoto (TEKNIK, 2008)
One of gender issues in architecture is domesticity, space in a home. According to feminist perspectivehome spatial design must be consider women’s spatial use for housework activities. Preliminaryresearch shows that mothers of a household tend to use kitchen, living room, and master bedroom intheir everyday activities so there must be connectedness appearance among those spaces. In fact, homedesign in Indonesia pays less attention to it. This research aimed to find out how far real-estatedeveloper accommodates the women’s spatial use for housework activities on their products. Data isobtained from 81 real estate advertisements on newspaper. The data is treated by content analysis tofind the offering items on the advertisement. The result show that 19% real- estate developers use facilityof housing and environment as superiority on their products and only 3.5% of them use householdspatial needs. It can be concluded that home design in Indonesia pay less attention to women’s spatialuse for housework activities